Structure and composition of the cloud forest in Copalillos, Luis Potosi, Mexico - Fortanelli-Martínez, Javier; García-Pérez, José; Castillo-Lara, Pedro (Instituto de Ecología, A.C., 2014)
The floristics and structure of a cloud forest in Copalillos, San Luis Potosí, is presented. Until very recently, this forest was not recorded in the existing cartography. A total of 199 species, corresponding to 165 genera and 91 botanical families, were recorded. The forest structure consists of three arboreal layers (upper, middle and lower), besides shrub and herbaceous strata. The dominant species in the upper tree stratum are Liquidambar styraciflua, Quercus germana and Q. pinnativenulosa. The main tree species of the middle level were Magnolia schiedeana, Persea liebmannii and Ilex rubra. The lower tree layer was largely dominated by Eugenia xalapensis. This relict represents an important link within the set of cloud forest areas located between Hidalgo and Tamaulipas.